2013
DOI: 10.1080/15257770.2012.744036
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Buffers in Cyanogen Bromide-Induced Ligations

Abstract: Rapid, template-directed ligation reactions between a phosphate-terminated oligonucleotide and an unphosphorylated reaction partner may be induced by cyanogen bromide (BrCN). Frequently, however, the reaction is low yielding, and even a large excess of the condensing agent can fail to induce quantitative conversions. In this study, we used BrCN to induce chemical primer extension reactions. Here, we report that buffers containing hydroxyl groups react with short oligodeoxynucleotides in the presence of BrCN. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Control reactions confirmed that the reactivity of aminoterminal strands is higher than that for strands with a 3′‐hydroxy group. When the ligation shown in Figure A was performed with a version of strand 1 that had a conventional deoxynucleoside at its 3′ terminus, incomplete conversion of the starting materials was found, even when the reaction time was extended from 3 to 24 h. This was also true for ligations with cyanogen bromide as the condensing agent, as well as for reactions induced by EDC . In all cases, no ligation product was detected in the absence of a template (Scheme S1 and Fig‐ ures S13–S16).…”
Section: Resultsmentioning
confidence: 88%
“…Control reactions confirmed that the reactivity of aminoterminal strands is higher than that for strands with a 3′‐hydroxy group. When the ligation shown in Figure A was performed with a version of strand 1 that had a conventional deoxynucleoside at its 3′ terminus, incomplete conversion of the starting materials was found, even when the reaction time was extended from 3 to 24 h. This was also true for ligations with cyanogen bromide as the condensing agent, as well as for reactions induced by EDC . In all cases, no ligation product was detected in the absence of a template (Scheme S1 and Fig‐ ures S13–S16).…”
Section: Resultsmentioning
confidence: 88%
“…The yield of enzyme-free chain extension is also dependent on the nucleophile found at the primer terminus. For straight DNA primers, no broadly applicable method exists for extension ( 21 ), but RNA primers with their terminal 2′/3′-diol are sufficiently reactive for extension to occur when allowed to react with monomers activated by one of the methods producing nucleotides with heterocyclic leaving groups. Still, the low reactivity of the ribose terminus often causes hydrolysis to compete successfully with extension, resulting in significant concentrations of free nucleotides that act as competitive inhibitors ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its buffering pH range (6.40 < pH < 7.80) makes BES suitable for biological studies. Recent studies describe the use of BES for this purpose [11][12][13][14][15]. There is evidence that BES complexes with Cu(II) [16]; however, this study only describes formation of CuL species.…”
Section: Introductionmentioning
confidence: 98%